Implementasi Kebijakan Program Kartu Prakerja di Tengah Pandemik Corona Virus Desease 19 di Kota Palembang - Fani, Tedy Dwi; Mudasir, Mudasir; Iriani, Atrika (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
In the Process of Implementing the Pre-Employment Card Program Policy in the midst of the Corona Virus Disease 19 Pandemic In Palembang City, implementation stages/processes are required. The purpose of this study was to analyze the implementation of the Pre-Employment Card Program Policy in the midst of the Corona Virus Disease 19 Pandemic in the city of Palembang. Problems in research The number of obstacles that arise starting from the registration process and then adding many applicants who are not the target of the program and some training cannot be completed so that incentives cannot be disbursed, it is necessary to involve the District/City Government through the relevant Office, namely the Manpower Office, which is more aware of the regional roadmap Results The research and findings are as follows: Implementation of the Pre-Employment Card Program Policy is seen from: 1) Whether or not the problem is easy to control is that knowledge and socialization are not optimal because there is a gap between people who know technology and those who don't, there are indications that it is not right on target, there are still findings of non-required categories The main recipients of Pre-Employment Cards and the dependence of Pre-Employment Card recipients on incentives alone. 2) The ability of policies to structure the implementation process; Implementing the Prakejra Card refers to the guidelines of Perpress No. 76 of 2020, this concept reveals how the changes in competence. Inappropriate use of incentives. 3) Variables outside the policy that affect the implementation process; Participants and recipients of Pre-Employment Cards are burdened with having to have at least a smartphone or computer to support online training and an adequate network. Responding to the continued implementation of the Pre-Employment Card program, it is still seen only as social assistance.